21st Century Educational Transformation and Graduate Quality: A Case Study of Ma'had Darussalam - Ummu Jauharin Farda; Nurul Azizah; Wahyu Arif Raharjo; Linda Indiyarti Putri; Abdul Rahman bin Ibrahim; Laili Fauziya (Universitas Wahid Hasyim Semarang, 2026)
This study aims to analyze the 21st-century educational transformation at Ma'had Darussalam, particularly in the implementation of a deep learning approach to graduate quality. The study used a descriptive qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving the school's leadership, teachers, students, and academic document managers. Data analysis was conducted using thematic analysis to identify key themes related to educational transformation. The results show that Ma'had Darussalam is gradually integrating 21st-century competencies through strengthening 4C skills, technological literacy, and life and career skills in learning and educational management. This implementation is supported by curriculum development, teacher capacity building, and student habituation activities that encourage independence, responsibility, and career readiness. The novelty of this study lies in the study of the transformation of Islamic education based on a deep learning approach in the context of Islamic educational institutions in Vietnam, which has been little researched. This study contributes as a reference for the development of adaptive and globally competitive Islamic education. However, this research is limited to one study location, so the findings cannot be generalized widely.